Protists are key players in the utilization of protein nitrogen in the arbuscular mycorrhizal hyphosphere - Vaishnav, Anukool; Rozmoš, Martin; Kotianová, Michala; Hršelová, Hana; Bukovská, Petra; Jansa, Jan (The New phytologist, 2025)
While largely depending on other microorganisms for nitrogen (N) mineralization, arbuscular mycorrhizal fungi (AMF) can transfer N from organic sources to their host plants. Here, we compared N acquisition by the AMF hyphae from chitin and protein sources and assessed the effects of microbial interactions in the hyphosphere. We employed in vitro compartmented microcosms, each containing three distinct hyphosphere compartments amended with different N sources (protein, chitin, or ammonium chloride), one of which was enriched with 15N isotope. All hyphosphere compartments were supplied with Paenibacillus bacteria, with or without the protist Polysphondylium pallidum. We measured the effect of these model microbiomes on the efficiency of 15N transfer to roots via the AMF hyphae. We found that the hyphae efficiently took up N from ammonium chloride, competing strongly with bacteria and protists. Mobilization of 15N from chitin and protein was facilitated by bacteria and protists, respectively. Notably, AMF priming significantly affected the abundance of bacteria and protists in hyphosphere compartments and promoted mineralization of protein N by protists. Subsequently, this N was transferred into roots. Our results provide the first unequivocal evidence that roots can acquire N from proteins present in the AMF hyphosphere and that protists may play a crucial role in protein N mineralization.
Keywords: Mycorrhizae; Nitrogen Isotopes; Nitrogen; izotopy dusíku; chitin; Plant Roots; Eukaryota; Hyphae; rostlinné proteiny; kořeny rostlin; multitrophic interactions; Chitin; organic nitrogen; temporal dynamics; dusík; hyphosphere; quantitative real‐time PCR; arbuscular mycorrhizal fungus; mykorhiza; stable isotopes; Plant Proteins; hyfy